The Role of Cervical Erosion on Vaginal Colonization of Candida sp. Study on the Intrauterine Contraceptive Device Users in Puskesmas Depok I Sleman - Satiti Retno Pudjiati, Erni Setyawati, Fajar Waskito (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2009)
Background: Candida sp is an opportunistic pathogenic yeast causing clinical diseases such as vulvovaginal candidiasis (VVC) under certain circumstances. Availability of erythrocytes in the vagina, as in cervical erosion, creates an ideal niche for yeast possessing erythrocyte-binding surface receptors to enhance colonization of Candida sp. Objective: To compare the number of vaginal Candida sp colonies among IUD users with and without cervical erosion. Methods: It was a cross-sectional study involving 45 IUD users. Subjects were classified into cervical erosion group and without cervical erosion group, who underwent vaginal lavage to obtain vaginal fluid samples. Candida sp were grown by inoculating 0.1 ml of vaginal fluid samples into CEA culture media and incubated at 25Â°C-30Â°C for 48 hours. Candida sp would grow as round and smooth colonies in blackish-brown color. The numbers of colonies (cfu/ml) in each CEA disk were measured manually, and multiplicated with the factors of dilution. Data were numeric variables, and analyzed with Students t-test. Results: Average number of Candida sp colonies in the group with cervical erosion was 154.25:t 102.61 cfulml, while that in the group without cervical erosion was 47.00:t 39.08 cfulml. Conclusion: Average number of Candida sp colonies in IUD users with cervical erosion was significantly higher than in IUD users without cervical erosion (p < 0.05). Key words: cervical erosion - Candida sp - VVC - yeast possessing erythrocyte-binding receptors -IUD